Sonar based navigation system for an underwater vehicle - Smith, R; Frost, A; Probert, P (Soc Underwater Technol, 1998)
This paper describes the design and development of a navigation system for a small remotely operated underwater vehicle (ROV). The navigation system uses sonar to localise the vehicle with respect to underwater structures. The navigation system has been successfully implemented. This has required careful construction of an estimator. Through implementation, we have shown that, with sufficient sensor information, a relatively straight-forward vehicle model is sufficient. This is beneficial both in reduced computation time, and since it involves a small number of easily measurable physical parameters. Experimental results are shown for the localisation system combined with a simple control system.